Pemanfaatan Ruang Terbuka Publik Taman Alun Melayu Kapuas Untuk Melakukan Aktivitas Olahraga Rekreasi - Syahadatina; Hardika, Nevi (Universitas PGRI Pontianak, 2023)
Recreational sports are physical activities carried out for pleasure that have benefits for physical fitness. Recreational sports can be done in spare time or to fill time off. This study aims to determine the use of public open space in the Kapuas Malay Alun Park for recreational sports activities. This research was conducted at Taman Alun Melayu Kapuas in Pontianak with the research subjects being visitors to Taman Alun Melayu Kapuas who agreed to be interviewed. Data collection techniques and instruments used in the form of observation, interviews and documentation. The results of the interviews were 1) Availability of good facilities in the form of playgrounds, water parks, sports facilities, and sitting gardens, 2) The development of activities in the Kapuas Malay Alun Park was influenced by the location's attractiveness in the form of facilities and infrastructure, visitors not only from the local area but from outside areas also visit, and facilities, and 3) Strategies for utilizing facilities based on natural beauty and the availability of infrastructure in the Kapuas Malay Square Park.